Electron-related optical properties in T-shaped AlxGa1−xAs/GaAs quantum wires and dots (2015)
ABSTRACT: The electronic structure and the intersubband optical absorption and relative refractive index change coefficients in T-shaped two-dimensional quantum dot and one-dimensional quantum wire are studied. The T-shaped quantum dot is embedded in AlxGa1−xAs, with x = 0.35, the arm region has x = 0 whereas different values of the Al molar fraction are present for the T-stem region (x = 0, 0.7, 0.14, and 0.21). The model calculation is useful for studying both a 1D quantum wire of T-shaped cross- section and a 2D T-shaped quantum dot. The conduction and valence band states are described within the effective mass and parabolic band approximations. The agreement between calculated photoluminescence peak energy transitions and previously reported experimental values in such T-shaped quantum well wires is discussed. The electron-related optical coefficients are calculated using a density-matrix expansion with the inclusion of the linear and third-order nonlinear contributions to the dielectric susceptibility. The results for this optical response are presented as functions of the Al molar fraction, as well as of the polarization, and intensity of the incident light.